Dinamika Penalaran Konsep Pendidikan pada Masyarakat - Kurnia Dwi Putri; Nur’aini Nur’aini; Nova Ayu Ningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Democratization of education can be actualized through, among others, the application of the concept of community-based education. Community-based education is a system of education in which the community makes a high proportion of decisions concerning education, starting from matters of the input, process, and output through to the financing of education .This article is philosophically aimed at exploring the basic ideas and concepts implied in community-based education.The understanding of the community, especially parents, on the awareness of the importance of education needs to be improved through an emotional approach. This is done in order to be able to provide a good education, between education in schools, families, and in the community, and to encourage the community to consider encouraging children to get education to a higher level, to equip children as the nation's next generation. The community environment is very influential in improving children's education, as well as the family environment. This research aims to gain public awareness of the importance of children's education. The method used is descriptive research method, which focuses on problems that are appropriate at the time the research takes place. In this study, the presentation of data using observation and interview techniques.